PENGGUNAAN ALAT MUSIK MELODIS DALAM PENINGKATAN PEMBELAJARAN SENI MUSIK - nur, rendra (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Rendra Nurwidodo1, H. Setyo Budi2, Triyono3 FKIP PGSD Universitas Sebelas Maret 1 Mahasiswa S1 PGSD FKIP UNS 2,3 Dosen S1 PGSD FKIP UNS e-mail: dra.ren@rocketmail.com Abstract: The using of melodic Musical Arts in improving Music Learning fourth grade students Kajoran Kebumen District 1 Academic Year 2012/2013. The purposes of this study to describe the using of tuned instrument and improve of tuned instrument in art music learning fourth grade students of SD Negeri 1 Kajoran school year 2012/2013. This research is a classroom action research (CAR). The experiment was conducted in three cycles. The subjects were all students in the fourth grade class of SDN 1 Kajoran which amounts to 33 students. Source data came from students, peers, and researchers. Data collection techniques using observation, documentation, and testing. The validity of the data using triangulation techniques and triangulation of sources. Data analysis with qualitative and quantitative analysis. The results showed that through the use of tuned instrument can improve the art of music learning from pre cycle to the first cycle, second cycle and third cycle. Keywords: tuned instrument, improving learning, the art of music. Abstrak: Penggunaan Alat Musik melodis dalam Peningkatan Pembelajaran Seni Musik Siswa kelas IV SD Negeri 1 Kajoran Kabupaten Kebumen Tahun Ajaran 2012/2013. Tujuan penelitian ini adalah untuk mendiskripsikan penggunaan alat musik melodis dan meningkatkan pembelajaran seni musik siswa kelas IV SD Negeri 1 Kajoran tahun ajaran 2012/2013. Penelitian ini merupakan penelitian tindakan kelas (PTK). Penelitian dilaksanakan dalam tiga siklus. Subjek penelitian ini adalah seluruh siswa kelas kelas IV SDN 1 Kajoran yang berjumlah 33 siswa. Sumber data berasal dari siswa, teman sejawat, dan peneliti. Teknik pengumpulan data menggunakan observasi, dokumentasi, dan tes. Validitas data menggunakan triangulasi teknik dan triangulasi sumber. Analisis data yang digunakan dengan analisis kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa melalui penggunaan alat musik melodis dapat meningkatkan pembelajaran seni musik dari prasiklus ke siklus I, siklus II, dan siklus III. Kata kunci: Alat Musik Melodis, Peningkatan Pembelajaran, Seni Musik.